Contribution of Interest in Learning to Learning Outcomes in Social Studies Subjects for Grade IV Students of SD Negeri Bulusidokerto Sidoarjo - Didik Hermanto (Madrosatuna: Journal of Islamic Elementary School, 2017)
The study aims to determine the contribution and analyze the level of contribution of interest in learning to the learning outcomes of social studies students of fourth grade SD Negeri Bulusidokare Sidoarjo. The design of the study used quantitative correlation type research. Research sample of grade IV students of SD Negeri Bulusidokare Sidoarjo. Data collection techniques using questionnaires and documentation. Data analysis techniques using product moment correlation test to reveal the contribution and test the determination to reveal the level of contribution. Based on the presentation and analysis of the data, it can be concluded: 1) there is a contribution of interest in learning to the learning outcomes in social studies of fourth grade students of SD Negeri Bulusidokare Sidoarjo of 0.97, meaning that interest in learning has a very strong correlation to student learning outcomes and 2) there is a contribution the high between interest in learning towards learning outcomes in subjects of class IV IPS of SD Negeri Bulusidokare Sidoarjo is 94%.